Bacillus velezensis GX1 and its potential for the control of lily bulb rot - Sha Zhang; Ting Lou; Si Wu; Shenggui Liu; Hao Pan; Jing Yang; Yifeng Su; Wang Hu; Wei Xiang; Shuangyan Pan; Lei Sun (Biological Control)
Bulb rot of lily (Lilium brownii var. viridulum), caused by Fusarium commune, is a serious soilborne disease of lily plants. In this study, several bacterial isolates were obtained from the rhizosphere of healthy lily plants and evaluated for biocontrol potential. Among the obtained isolates, GX1 had the highest level of antifungal activity in vitro, inhibiting the growth of F. commune by 52.0 %, relative to the control (CK). The isolate was identified as Bacillus velezensis based on its morphology and 16S rRNA and gyrB gene sequence analysis. The fermentation broth of GX1 after 12 d of fermentation at 25 °C (pH 7) exhibited strong antifungal activity. A crude lipopeptide extracts of GX1 fermentation broth was as effective (50.3 %) at inhibiting the mycelial growth of F. commune as living cultures of GX1. GX1 possesses fenD, bmyB, srfAA and bacA antimicrobial peptide (AMP) genes, which may be the primary source of its antifungal activity. GX1 significantly reduced the disease severity index of lily bulb rot in pot experiments, indicating that B. velezensis GX1 has substantial potential for the biological control of lily bulb rot.